Business Start-ups by the Unemployed - an Econometric Analysis Based on Firm Data - Friedhelm Pfeiffer; Frank Reize (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1998)
This study investigates firm survival and employment growth of start-ups by unemployed people in East and West Germany as promoted by the Work Support Act (so called bridging allowances). In 1994, the services provided were improved considerably, which led to a sharp increase in the number of start-ups by the unemployed. The empirical analysis is based on a sample of newly founded firms from the ZEW Firm Start-up Panel. The sample contains firms which were founded between 1993 and 1995 and could be observed at least one year after their foundation in 4 regions of East and 11 regions of West Germany. In the econometric analysis, self-selection effects are taken into account by using simultaneous models of start-up promotion and firm development. While firm survival seems to be negatively affected by foundation from unemployment, especially in the East German regions, an influence on employment growth is not evident.
Keywords: C35; D92; J68; M13; 330